Long Non-Coding RNA Malat-1 Is Dispensable during Pressure Overload-Induced Cardiac Remodeling and Failure in Mice - Peters, Tim; Hermans-Beijnsberger, Steffie; Beqqali, Abdelaziz; Bitsch, Nicole; Nakagawa, Shinichi; Prasanth, Kannanganattu V.; de Windt, Leon J.; van Oort, Ralph J.; Heymans, Stephane; Schroen, Blanche (PLOS ONE, 2016)
Background Long non-coding RNAs (lncRNAs) are a class of RNA molecules with diverse regulatory functions during embryonic development, normal life, and disease in higher organisms. However, research on the role of lncRNAs in cardiovascular diseases and in particular heart failure is still in its infancy. The exceptionally well conserved nuclear lncRNA Metastasis associated in lung adenocarcinoma transcript 1 (Malat-1) is a regulator of mRNA splicing and highly expressed in the heart. Malat-1 modulates hypoxia-induced vessel growth, activates ERK/MAPK signaling, and scavenges the anti-hypertrophic microRNA-133. We therefore hypothesized that Malat-1 may act as regulator of cardiac hypertrophy and failure during cardiac pressure overload induced by thoracic aortic constriction (TAC) in mice. Results Absence of Malat-1 did not affect cardiac hypertrophy upon pressure overload: Heart weight to tibia length ratio significantly increased in WT mice (sham: 5.78±0.55, TAC 9.79±1.82 g/mm; p<0.001) but to a similar extend also in Malat-1 knockout (KO) mice (sham: 6.21±1.12, TAC 8.91±1.74 g/mm; p<0.01) with no significant difference between genotypes. As expected, TAC significantly reduced left ventricular fractional shortening in WT (sham: 38.81±6.53%, TAC: 23.14±11.99%; p<0.01) but to a comparable degree also in KO mice (sham: 37.01±4.19%, TAC: 25.98±9.75%; p<0.05). Histological hallmarks of myocardial remodeling, such as cardiomyocyte hypertrophy, increased interstitial fibrosis, reduced capillary density, and immune cell infiltration, did not differ significantly between WT and KO mice after TAC. In line, the absence of Malat-1 did not significantly affect angiotensin II-induced cardiac hypertrophy, dysfunction, and overall remodeling. Above that, pressure overload by TAC significantly induced mRNA levels of the hypertrophy marker genes Nppa, Nppb and Acta1, to a similar extend in both genotypes. Alternative splicing of Ndrg2 after TAC was apparent in WT (isoform ratio; sham: 2.97±0.26, TAC 1.57±0.40; p<0.0001) and KO mice (sham: 3.64±0.37; TAC: 2.24±0.76; p<0.0001) and interestingly differed between genotypes both at baseline and after pressure overload (p<0.05 each). Conclusion These findings confirm a role for the lncRNA Malat-1 in mRNA splicing. However, no critical role for Malat-1 was found in pressure overload-induced heart failure in mice, despite its reported role in vascularization, ERK/MAPK signaling, and regulation of miR-133.